Picky, hungry eaters in the cold: persistent substrate selectivity among polar pelagic microbial communities - Steen, Andrew D.; Arnosti, Carol (Frontiers in Microbiology, 2014)
Polar pelagic microbial communities access a narrower range of polysaccharide substrates than communities at lower latitudes. For example, the glucose-containing polysaccharide pullulan is typically not hydrolyzed in fjord waters of Svalbard, even though pullulan is rapidly hydrolyzed in sediments from Svalbard fjords, other polysaccharides are hydrolyzed rapidly in Svalbard waters, and pullulan is hydrolyzed rapidly in temperate waters. The purpose of this study was to investigate potential factors preventing hydrolysis of pullulan in Svalbard fjord waters. To this end, in two separate years, water from Isfjorden, Svalbard, was amended with different carbon sources and/or additional nutrients in order to determine whether increasing the concentration of these potentially-limiting factors would lead to measurable enzymatic activity. Addition of nitrate, phosphate, glucose, or amino acids did not yield detectable pullulan hydrolysis. The only treatment that led to detectable pullulan hydrolysis was extended incubation after the addition of maltotriose (a subunit of pullulan, and potential inducer of pullulanase). In these fjords, the ability to enzymatically access pullulan is likely confined to numerically minor members of the pelagic microbial community. These results are consistent with the hypothesis that pelagic microbial communities at high latitudes exhibit streamlined functionality, focused on a narrower range of substrates, than their temperate counterparts.